Post Partum Midwifery Care in Ny. D P: Ii A: 0 At The Eliza Bestari Sinaga Midwifery Clinic, Sst M.Kes West Kisaran District Asahan District Year 2020 - Larasati Wulandari, Bayu (International Journal on Health and Medical Sciences, 2022)
The postpartum period (puerperium) begins after the placenta is born and ends when the uterine organs return to their pre-pregnancy state which lasts for 6 weeks or 42 days. Postpartum maternal health services are health services for postpartum mothers according to standards, which are carried out at least 4 times according to the recommended schedule, namely at six to 8 hours after delivery, on the sixth day after delivery, at 2 weeks after delivery and at 6 weeks postpartum.It is estimated that 60% of maternal deaths due to pregnancy occur after delivery and 50% of postpartum deaths occur within the first 24 hours. Maternal deaths during the postpartum period are usually caused by postpartum infections (10%), this occurs due to lack of wound care, bleeding (42%) due to tearing of the birth canal, retained placenta and uterine otonia, eclampsia (13%) and postpartum complications (11% ). Postpartum care is very necessary because this period is a critical period for both mother and baby (Lidya, 2017). Postpartum visits are carried out to assess the health condition of the mother and baby, prevent health problems, detect complications and deal with problems that occur.